52 Incidence and outcomes of bailout stenting following use of sirolimus drug coated balloon. (17th July 2020) - Khattak, Sophia; Liu, Boyang; Ishaq, Mohammed; Athukorala, Sampath; Watkin, Richard; Lee, Kaeng; Pulikal, George; Ment, Jerome; Bhatia, Gurbir; Freestone, Beth; Pitt, Michael; Vigano, Elena
Abstract : Introduction: Bailout stenting post-Paclitaxcel drug coated balloon use (DCB) is done with Limus eluting stent as we don't use Paclitaxcel eluting stent anymore. However, when using Sirolimus DCB, bailout stenting is done with Limus eluting stent, but this raises the issue of drug toxicity with double dose of Limus to the vessel wall. In this study, we evaluate all patients treated with Limus DCB that required bailout stenting for safety and clinical outcomes. Methods and Results: We evaluated all patients who were treated with MagicTouch Sirolimus eluting DCB (Concept Medical limited, India) March 2018-June 2019. Bailout stenting per lesion were identified and studied for endpoints which included cardiac death, target vessel MI, stent thrombosis, target lesion revascularisation and MACE. Between the study period; 406 patients (477-lesions) with a mean age of 66 ± 11.2 years (range; 37-90) were treated with MagicTouch DCB. Bailout stenting was required in 39 lesions (8%) and of which 22 were due to dissections and 17 were due to >50% recoil following DCB use. During a median follow-up of 302 days; there were no cases of cardiac death, 1-case of target vessel MI (2.6%) and 3-cases (7%) of TLR. The MACE rate was 7%. There were no cases of stent thrombosis as per the ARC definition. Conclusion: One of the highlighting features of our study is low-rates of bailout stenting (9%). This may be due to our criteria of not stenting mild dissections (unless they are flow limiting) and not to expect stent like results. The outcomes in the bailout stenting group is excellent with very low hard clinical endpoints indicating there may not be any toxic effect from double dose of Limus drug (DCB + DES). Conflict of Interest: None